Proposta de aplicação de visão computacional na análise de exercícios de musculação: Utilização da biblioteca Mediapipe com o modelo Blazepose e arquitetura Web multiplataforma - Moraes, João Antonio de Brito; Santos, Lucas Araujo dos; Bohm, Natthalie; Araujo, Renan Cesar de; Baptista, Gabriel Lara (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the Web, 2025)
This research presents the development of a Proof of Concept for the use of the MediaPipe library and the BlazePose model in creating a computer vision application aimed at monitoring the execution of strength training exercises. The system is built on a web-based, cross-platform architecture, and all image analysis is done in the Front-end layer by using a Javascript shell. The results were satisfactory, and there are clear goals for future implementations to evolve the solution into a robust and viable product.